Double-layer pressure-bearing pipe and preparation method thereof
The pressure bearing of existing pipes under high temperature and high pressure conditions is solved by using modified hollow glass microspheres, glass fiber/basalt fiber composite tapes and amination-modified SiO2/CeO2 composite fillers in double-layer pressure-bearing pipes. The problems of reduced capacity and insufficient outer layer performance achieve higher pressure bearing strength, durability and corrosion resistance.
Patent Information
- Application Number
- CN202510045790.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing double-layer pressure-bearing pipes have reduced pressure-bearing capacity under high temperature and high pressure conditions, and the corrosion resistance and aging resistance of outer polyethylene are not sufficient to meet the long-term high-strength application needs.
The preparation method of double-layer pressure-bearing pipe is adopted. The inner layer is mixed with modified hollow glass microspheres and high-density polyethylene to increase the winding of the glass fiber/basalt fiber composite belt, and the outer layer is aminated modified SiO2/CeO2 composite. The filler serves as a protective layer.
It improves the pressure bearing strength, durability and corrosion resistance of the pipe, enhances the performance of the pipe under high temperature and high pressure conditions, and improves the bending strength and impact strength of the outer protective layer.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pipes, and in particular to a double-layer pressure-bearing pipe and a preparation method thereof. Background Art
[0002] The application of metal reinforced composite pipes is relatively common, but the corrosion of metals and the difficulty in recycling waste composite pipes restrict their development. Therefore, non-metal reinforced composite pipes have become a hot topic of research. Reinforced thermoplastic composite pipes are a new type of plastic pipes in recent years, which have attracted great attention from various countries and have developed rapidly. Its main advantages are pressure resistance, corrosion resistance, light weight and low cost. It can well overcome the corrosion problem of steel pipes and the pressure resistance problem of plastic pipes. It is mainly used in oil and natural gas extraction, high-pressure long-distance natural gas transportation and various pipeline fields that require high-pressure medium transportation.
[0003] In the experimental study on the high temperature resistance of aramid fiber reinforced PE-RT pipe, Natural Gas Industry, 2015 Issue 35, a flexible composite pipe with a lining layer of high temperature polyethylene (PE-RT) and a reinforcement layer of aramid fiber was studied. The results show that high temperature has little effect on the mechanical properties of the lining layer PE-RT of the flexible composite pipe, but has a significant effect on the tensile properties of the reinforcement layer aramid fiber and the water pressure burst of the entire pipe, resulting in a decrease in the pressure bearing capacity of the entire pipe. Under the action of internal pressure, the aramid fiber of the reinforcement layer deformed and broke; in addition, the outer layer is generally made of polyolefin, and polyethylene is currently the most common. If only polyethylene is used as the outer layer, its performance may not be sufficient to meet the long-term and high-intensity application requirements when facing high temperature, chemical corrosion, compressive strength, aging resistance and other requirements.
[0004] Therefore, it is necessary to provide a method for preparing a double-layer pressure-bearing pipe to solve the problems existing in the above-mentioned prior art. Summary of the invention
[0005] In view of this, the present invention provides a double-layer pressure-bearing pipe and a preparation method thereof, which can improve the pressure-bearing strength while achieving durability and corrosion resistance.
[0006] To achieve the above purpose, the specific technical solutions provided by the present invention are as follows: The preparation method of the double-layer pressure-bearing pipe comprises the following steps: S1, soaking the continuous glass fiber bundle and the pretreated basalt fiber in a composite coupling agent ethanol solution for surface treatment, vacuum drying, pouring into a composite mold and mixing with molten high-density polyethylene, and pressing into a strip by a roller to obtain a glass fiber / basalt fiber composite strip; S2, mixing molten high-density polyethylene and modified hollow glass microspheres at high speed to obtain HGM / HDPE composite material, extruding the molten HGM / HDPE composite material through an extruder to obtain an inner layer pipe embryo, winding a glass fiber / basalt fiber composite tape on the inner layer pipe embryo, and compounding at 380-400° C. to obtain a composite inner layer pipe; S3. Mix the preheated epoxy resin and butyl glycidyl ether at a low speed, add diaminodiphenylmethane and stir at a high temperature, stir the aminated SiO2 / CeO2 composite filler at a high speed to mix evenly, spray it on the outer surface of the composite inner layer pipe to form an outer protective layer, cure it at a high temperature, and finally obtain a double-layer pressure-bearing pipe.
[0007] The inner layer of the present invention is double-layered and pressure-resistant. The inner layer embryo adds modified hollow glass microspheres (HGM) to high-density polyethylene (HDPE). The hollow glass microspheres have the characteristics of low density, high strength, and low thermal conductivity. However, the polarity difference between the hollow glass microspheres and the polymer matrix is large, which makes the compatibility of the hollow glass microspheres with high-density polyethylene weak. The modified hollow glass microspheres increase the compatibility between the hollow glass microspheres and the polyethylene resin, and promote the dispersion of the hollow glass microspheres in the high-density polyethylene matrix, so that the hollow glass microspheres in the inner layer embryo prepared by the HGM / HDPE composite material are evenly distributed. When encountering instantaneous high pressure or impact force, the high-density polyethylene can disperse the impact energy and reduce the risk of local damage. Therefore, the addition of modified hollow glass microspheres can improve the impact resistance of the composite pipe, thereby improving its pressure resistance performance under dynamic loads, and making the overall material lighter.
[0008] The present invention further enhances the static compressive strength of the overall composite pipe by winding a glass fiber / basalt fiber composite tape on the surface of the inner layer embryo, and uses a composite coupling agent as an activator to activate the glass fiber and the basalt fiber, so that the thickness of the glass fiber and the basalt fiber are relatively uniform, and the tension force is consistent, so that the inner layer pipe after the glass fiber / basalt fiber composite tape is wound has uniform and stable pressure resistance values at various locations on the pipe wall; and the glass fiber / basalt fiber composite tape is more tightly bonded to the high-density polyethylene after being treated, and the bonding strength between the glass fiber / basalt fiber composite tape and the inner layer embryo is further improved.
[0009] The present invention prepares the outer protective layer, and uses the aminated modified SiO2 / CeO2 composite filler as the filler to improve the overall durability and corrosion resistance. The silicon dioxide has hydrophobicity and thermal stability due to the high bond energy Si-O bond. In addition, CeO2 has a unique redox property, which can be transformed between different oxidation states, especially Ce 3+ and Ce 4+The mutual conversion between them makes it antioxidant and anti-corrosion. It no longer uses traditional polyethylene as the base material, but epoxy resin as the base material, which gives the overall higher heat resistance. The aminated SiO2 / CeO2 composite filler undergoes a ring-opening reaction with the epoxy groups in the epoxy resin due to the presence of amino groups to form a stable chemical cross-linking structure. This chemical bonding makes the interface between the inorganic filler and the resin stronger, further enhancing the bending strength and impact strength of the outer protective layer.
[0010] Optionally, the pretreated basalt fiber in step S1 is prepared by adding chopped basalt fiber material into a sulfuric acid solution with a mass concentration of 3%, stirring the mixture for reaction at 80° C. for 30 minutes, taking it out, filtering it, and drying it.
[0011] Optionally, the vacuum drying time in step S1 is 12 hours and the temperature is 80°C; the composite coupling agent ethanol solution is prepared by mixing a titanate coupling agent and a silane coupling agent in a volume ratio of 1:1 to prepare a composite coupling agent, adding the composite coupling agent to an ethanol solution with a volume concentration of 90%, mixing evenly, and adjusting the pH value to about 5.0 with glacial acetic acid; wherein the model of the titanate coupling agent is CS201, and the model of the silane coupling agent is KH540.
[0012] The present invention uses KH540 and CS201 as composite coupling agents to prepare modified hollow glass microspheres, wherein the amino group of KH540 generates new covalent bonds with resin molecules, and the long hydrocarbon chain of CS201 is entangled with high-density polyethylene through van der Waals force, and this entanglement can transmit stress effects, thereby playing a reinforcing role. The presence of hydrophobic groups with long carbon chains in the titanate CS201 increases the compatibility between the hollow glass microspheres and the high-density polyethylene, and further improves the dispersibility of the hollow glass microspheres.
[0013] Optionally, the modified hollow glass microspheres in step S2 are prepared by mixing a composite coupling agent ethanol solution and a hollow glass microsphere suspension, stirring the mixture by magnetic force, separating the mixture by vacuum filtration, washing the mixture 3 to 5 times with an ethanol solution, and drying the mixture under vacuum.
[0014] Optionally, the magnetic stirring temperature is 60°C and the time is 4 hours, and the vacuum drying temperature is 80°C and the time is 12 hours; the hollow glass microsphere suspension is prepared by mixing an ethanol solution with a volume concentration of 90% and hollow glass microspheres, and then subjecting the mixture to ultrasonic treatment for 45 minutes.
[0015] Optionally, in step S2, the glass fiber / basalt fiber composite tape is wound on the inner layer tube blank in a cross-winding manner from both ends, and the wound tube obtained after winding is compounded at 380-400° C. to obtain a composite inner layer tube.
[0016] The present invention cross-winds glass fiber / basalt fiber composite tapes on the surface of the inner layer embryo to disperse stress so as to increase the annular rigidity and compressive strength of the pipeline.
[0017] Optionally, the aminated SiO2 / CeO2 composite filler in step S3 is prepared by uniformly mixing an ethanol solution having a volume concentration of 90% and 3-aminopropyltriethoxysilane, adding SiO2 and CeO2 and mixing evenly, stirring the mixture at 80°C for 4-6 hours, centrifuging for 5 minutes, discarding the supernatant and taking the precipitate, drying it at 80°C for 12-16 hours, grinding it to obtain SiO2 / CeO2-NH2, and dispersing the SiO2 / CeO2-NH2 in water.
[0018] The present invention prepares an aminated SiO2 / CeO2 composite filler, and utilizes 3-aminopropyltriethoxysilane to carry out aminated modification on SiO2 and CeO2, which not only retains the hydrophobicity and thermal stability of silicon dioxide but also retains the antioxidant and anti-corrosion properties of CeO2, and 3-aminopropyltriethoxysilane also improves the bonding strength of the organic-inorganic interface.
[0019] Optionally, after dispersing SiO2 / CeO2-NH2 in water, pretreated MWCNTs-COOH is added and mixed, followed by ultrasonic treatment for 10-20 min, reaction at 80°C for 6-10 h, washing, centrifugation, and drying at 80°C for 24-48 h, to finally obtain an aminated SiO2 / CeO2 composite filler; wherein the pretreated MWCNTs-COOH is obtained by mixing and stirring a MWCNTs-COOH aqueous dispersion, a 10% mass concentration of 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution, and a 10% mass concentration of 0.1 parts of N-hydroxysuccinimide aqueous solution for 10 min; and the MWCNTs-COOH aqueous dispersion is obtained by adding MWCNTs-COOH to water and ultrasonicating for 1 h.
[0020] The present invention utilizes 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution and N-hydroxysuccinimide aqueous solution to activate the -COOH group in MWCNTs-COOH, so that aminated SiO2 / CeO2 and MWCNTs-COOH are cross-linked together through an amide reaction, and multiple carbon nanotubes are introduced to manufacture a multi-level structure, so that SiO2 and CeO2 particles are attached to the surface of MWCNTs, presenting a wrapped or semi-wrapped form, which is conducive to forming a rough multi-level surface during the spraying process and enhancing the durability and firmness of the protective layer.
[0021] Optionally, in step S3, the low-speed mixing time is 30 to 60 minutes, the high-temperature stirring temperature is 60°C and the time is 20 to 30 minutes, the high-speed stirring time is 20 to 30 minutes, and the high-temperature curing temperature is 80 to 100°C and the time is 2 to 5 hours.
[0022] Optionally, the double-layer pressure-bearing pipe comprises the following raw materials in weight proportions: 50-60 parts of preheated epoxy resin, 40-50 parts of butyl glycidyl ether, 12-15 parts of diaminodiphenylmethane, 5-10 parts of MWCNTs-SiO2 / CeO2, and 100-120 parts of a composite inner layer pipe, wherein the composite inner layer pipe comprises the following raw materials in weight proportions: 80-100 parts of HGM / HDPE composite material and 50-60 parts of glass fiber / basalt fiber composite tape.
[0023] The above technical solution of the present invention includes at least the following beneficial effects: 1. The inner double-layer of the present invention is pressure-resistant. The inner layer embryo is prepared by adding modified hollow glass microspheres to high-density polyethylene. The hollow glass microspheres have the characteristics of low density, high strength and low thermal conductivity. The modified hollow glass microspheres promote the dispersion of the hollow glass microspheres in the high-density polyethylene matrix. The addition of the modified hollow glass microspheres improves the impact resistance of the composite pipe, thereby improving its pressure resistance performance under dynamic load and making the overall material lighter.
[0024] 2. The present invention further enhances the static compressive strength of the overall composite pipe by winding a glass fiber / basalt fiber composite tape on the surface of the inner layer embryo, and uses a composite coupling agent as an activator to activate the glass fiber and basalt fiber. The prepared glass fiber / basalt fiber composite tape is treated to make it more tightly bonded to the high-density polyethylene, and further improves its bonding strength with the inner layer embryo.
[0025] 3. The present invention prepares the outer protective layer and utilizes aminated SiO2 / CeO2 composite fillers as fillers to improve the overall durability and corrosion resistance. Silicon dioxide has hydrophobicity and thermal stability due to the high bond energy Si-O bond. CeO2 has unique redox properties, which makes it antioxidant and corrosion resistant. Epoxy resin is used as the base material to give the overall higher heat resistance. The aminated SiO2 / CeO2 composite fillers form a stable chemical cross-linking structure with the epoxy resin due to the presence of amino groups, making the interface between the inorganic filler and the resin more solid, further enhancing the bending strength and impact strength of the outer protective layer. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0027] Preparation 100 g of chopped basalt fiber material was added into 300 mL of 3% sulfuric acid solution, and the mixture was stirred and reacted at 80° C. for 30 min, and then the mixture was taken out, filtered, and dried to obtain pretreated basalt fiber.
[0028] A titanate coupling agent (model: CS201) and a silane coupling agent (model: KH540) were mixed in a volume ratio of 1:1 to prepare a composite coupling agent. Seven parts of the composite coupling agent were added to 100 parts of an ethanol solution with a volume concentration of 90% and mixed evenly. The pH value was adjusted to about 5.0 with glacial acetic acid to obtain a composite coupling agent ethanol solution.
[0029] 20 parts of hollow glass microspheres (HGM) were added to 100 parts of ethanol solution with a volume concentration of 90%, and a hollow glass microsphere suspension was prepared by ultrasonic treatment for 45 minutes.
[0030] 0.2 parts of MWCNTs-COOH were added into 100 parts of water and ultrasonicated for 1 hour to obtain a MWCNTs-COOH aqueous dispersion.
[0031] 0.1 parts of 10% by mass concentration of 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution and 0.1 parts of 10% by mass concentration of N-hydroxysuccinimide aqueous solution were added to 10 parts of MWCNTs-COOH aqueous dispersion, and stirred at room temperature for 10 minutes to obtain pretreated MWCNTs-COOH.
[0032] Example 1 100 parts of continuous glass fiber bundles (Shandong Fiberglass Group Co., Ltd., 2400TEX, diameter 17μm) and 50 parts of pretreated basalt fibers were soaked in 150 parts of composite coupling agent ethanol solution for surface treatment, dried in a vacuum oven at 80°C for 12 hours, and excess moisture was removed. The mixture was poured into a composite mold and mixed evenly with 100-120 parts of molten high-density polyethylene (HDPE), and pressed into a strip by a roller to obtain a glass fiber / basalt fiber composite strip.
[0033] 65 parts of the composite coupling agent ethanol solution were added to 50 parts of the hollow glass microsphere suspension, and after magnetic stirring at 60°C for 4 hours, the mixture was separated by vacuum filtration, washed with ethanol solution for 3 times, and dried in a vacuum oven at 80°C for 12 hours to obtain the modified hollow glass microsphere (HGM). 100 parts of molten high-density polyethylene (HDPE) and 5 parts of modified hollow glass microspheres were mixed and stirred at high speed for 20-30 minutes to obtain the HGM / HDPE composite material. 80 parts of the molten HGM / HDPE composite material were extruded by an extruder to obtain the inner layer tube embryo, and 50 parts of the glass fiber / basalt fiber composite tape were wound on the inner layer tube embryo in a winding manner of cross winding from both ends, and the wound tube obtained after winding was compounded at 380°C to obtain the composite inner layer tube.
[0034] 2.6 parts of 3-aminopropyltriethoxysilane (model: KH-550) were added to 100 parts of 90% ethanol solution and mixed evenly, then 1 part of SiO2 and 2 parts of CeO2 were added and mixed evenly, stirred and reacted at 80°C for 4 hours, centrifuged for 5 minutes, the supernatant was discarded and the precipitate was dried at 80°C for 12 hours, and SiO2 / CeO2-NH2 was obtained after grinding; 1.5 parts of SiO2 / CeO2-NH2 were dispersed in 10 parts of water, 10 parts of pretreated MWCNTs-COOH were added and mixed, ultrasonically treated for 10 minutes, reacted at 80°C for 6 hours, washed, centrifuged, and dried at 80°C for 24 hours to obtain an aminated SiO2 / CeO2 composite filler.
[0035] Mix 50 parts of preheated epoxy resin (model: E51) and 40 parts of butyl glycidyl ether at low speed for 30 minutes, then add 12 parts of diaminodiphenylmethane DDM and stir at 60°C for 20 minutes, add 5 parts of MWCNTs-SiO2 / CeO2 and stir at high speed for 20 minutes. After mixing evenly, spray it evenly on the outer surface of the composite inner layer pipe to form an outer protective layer, and cure it at 80°C for 5 hours to finally obtain a double-layer pressure-bearing pipe.
[0036] Example 2 100 parts of continuous glass fiber bundles (Shandong Fiberglass Group Co., Ltd., 2400TEX, diameter 17μm) and 50 parts of pretreated basalt fibers were soaked in 150 parts of composite coupling agent ethanol solution for surface treatment, dried in a vacuum oven at 80°C for 12 hours, and excess moisture was removed. The mixture was poured into a composite mold and mixed evenly with 120 parts of molten high-density polyethylene (HDPE), and pressed into a strip by a roller to obtain a glass fiber / basalt fiber composite strip.
[0037] 65 parts of the composite coupling agent ethanol solution were added to 50 parts of the hollow glass microsphere suspension, and after magnetic stirring at 60°C for 4 hours, the mixture was separated by vacuum filtration, washed with ethanol solution for 5 times, and dried in a vacuum oven at 80°C for 12 hours to obtain the modified hollow glass microsphere (HGM). 120 parts of molten high-density polyethylene (HDPE) and 8 parts of modified hollow glass microspheres were mixed and stirred at high speed for 30 minutes to obtain the HGM / HDPE composite material. 100 parts of the molten HGM / HDPE composite material were extruded through an extruder to obtain the inner layer tube embryo, 60 parts of the glass fiber / basalt fiber composite tape were wound on the inner layer tube embryo in a winding manner of cross winding from both ends, and the wound tube obtained after winding was compounded at 400°C to obtain the composite inner layer tube.
[0038] 3.5 parts of 3-aminopropyltriethoxysilane (model: KH-550) were added to 100 parts of 90% ethanol solution and mixed evenly, then 2 parts of SiO2 and 3 parts of CeO2 were added and mixed evenly, stirred and reacted at 80°C for 6 hours, centrifuged for 5 minutes, the supernatant was discarded and the precipitate was dried at 80°C for 16 hours, and SiO2 / CeO2-NH2 was obtained after grinding; 1.5 parts of SiO2 / CeO2-NH2 were dispersed in 10 parts of water, 10 parts of pretreated MWCNTs-COOH were added and mixed, ultrasonically treated for 10 minutes, reacted at 80°C for 6 hours, washed, centrifuged, and dried at 80°C for 24 hours to obtain an aminated SiO2 / CeO2 composite filler.
[0039] 60 parts of preheated epoxy resin (model: E51) and 50 parts of butyl glycidyl ether were mixed at low speed for 60 minutes, and then 15 parts of diaminodiphenylmethane DDM were added and stirred at 60°C for 30 minutes. 10 parts of MWCNTs-SiO2 / CeO2 were added and stirred at high speed for 30 minutes. After mixing evenly, they were evenly sprayed on the outer surface of the composite inner layer pipe to form an outer protective layer. The mixture was cured at 100°C for 2 hours to finally obtain a double-layer pressure-bearing pipe.
[0040] Example 3 100 parts of continuous glass fiber bundles (Shandong Fiberglass Group Co., Ltd., 2400TEX, diameter 17 μm) and 50 parts of pretreated basalt fibers were soaked in 150 parts of composite coupling agent ethanol solution for surface treatment, dried in a vacuum oven at 80°C for 12 h, and excess moisture was removed. The mixture was poured into a composite mold and mixed evenly with 110 parts of molten high-density polyethylene (HDPE), and pressed into a strip by a roller to obtain a glass fiber / basalt fiber composite strip.
[0041] 65 parts of the composite coupling agent ethanol solution were added to 50 parts of the hollow glass microsphere suspension, and after magnetic stirring at 60°C for 4 hours, the mixture was separated by vacuum filtration, washed with ethanol solution 4 times, and dried in a vacuum oven at 80°C for 12 hours to obtain the modified hollow glass microsphere (HGM). 105 parts of molten high-density polyethylene (HDPE) and 5-8 parts of modified hollow glass microspheres were mixed and stirred at high speed for 25 minutes to obtain the HGM / HDPE composite material. 90 parts of the molten HGM / HDPE composite material were extruded through an extruder to obtain the inner layer tube embryo, and 55 parts of the glass fiber / basalt fiber composite tape were wound on the inner layer tube embryo in a winding manner of cross winding from both ends, and the wound tube obtained after winding was compounded at 390°C to obtain the composite inner layer tube.
[0042] Add 3 parts of 3-aminopropyltriethoxysilane (model: KH-550) to 100 parts of 90% ethanol solution and mix well, then add 1.5 parts of SiO2 and 2.5 parts of CeO2 and mix well, stir and react at 80°C for 5 hours, centrifuge for 5 minutes, discard the supernatant and take the precipitate, dry at 80°C for 14 hours, and grind to obtain SiO2 / CeO2-NH2; disperse 1.5 parts of SiO2 / CeO2-NH2 in 10 parts of water, add 10 parts of pretreated MWCNTs-COOH and mix, ultrasonically treat for 10 minutes, react at 80°C for 6 hours, wash, centrifuge, and dry at 80°C for 24 hours to obtain an aminated SiO2 / CeO2 composite filler.
[0043] Mix 55 parts of preheated epoxy resin (model: E51) and 45 parts of butyl glycidyl ether at low speed for 30-60 minutes, then add 13 parts of diaminodiphenylmethane DDM and stir at 60°C for 25 minutes, add 7 parts of MWCNTs-SiO2 / CeO2 and stir at high speed for 25 minutes. After mixing evenly, spray it evenly on the outer surface of the composite inner layer pipe to form an outer protective layer, and cure it at 90°C for 3 hours to finally obtain a double-layer pressure-bearing pipe.
[0044] Example 4 100 parts of continuous glass fiber bundles (Shandong Fiberglass Group Co., Ltd., 2400TEX, diameter 17 μm) and 50 parts of pretreated basalt fibers were soaked in 150 parts of composite coupling agent ethanol solution for surface treatment, dried in a vacuum oven at 80°C for 12 h, and excess moisture was removed. The mixture was poured into a composite mold and mixed evenly with 105 parts of molten high-density polyethylene (HDPE), and pressed into a strip by a roller to obtain a glass fiber / basalt fiber composite strip.
[0045] 65 parts of the composite coupling agent ethanol solution were added to 50 parts of the hollow glass microsphere suspension, and after magnetic stirring at 60°C for 4 hours, the mixture was separated by vacuum filtration, washed with ethanol solution 4 times, and dried in a vacuum oven at 80°C for 12 hours to obtain the modified hollow glass microsphere (HGM). 110 parts of molten high-density polyethylene (HDPE) and 6 parts of modified hollow glass microspheres were mixed and stirred at high speed for 30 minutes to obtain the HGM / HDPE composite material. 85 parts of the molten HGM / HDPE composite material were extruded by an extruder to obtain the inner layer tube embryo, 60 parts of the glass fiber / basalt fiber composite tape were wound on the inner layer tube embryo in a winding manner of cross winding from both ends, and the wound tube obtained after winding was compounded at 400°C to obtain the composite inner layer tube.
[0046] 2.7 parts of 3-aminopropyltriethoxysilane (model: KH-550) were added to 100 parts of 90% ethanol solution and mixed evenly, then 1 part of SiO2 and 3 parts of CeO2 were added and mixed evenly, stirred and reacted at 80°C for 5 hours, centrifuged for 5 minutes, the supernatant was discarded and the precipitate was dried at 80°C for 13 hours, and SiO2 / CeO2-NH2 was obtained after grinding; 1.5 parts of SiO2 / CeO2-NH2 were dispersed in 10 parts of water, 10 parts of pretreated MWCNTs-COOH were added and mixed, ultrasonically treated for 10 minutes, reacted at 80°C for 6 hours, washed, centrifuged, and dried at 80°C for 24 hours to obtain an aminated SiO2 / CeO2 composite filler.
[0047] 56 parts of preheated epoxy resin (model: E51) and 47 parts of butyl glycidyl ether were mixed at low speed for 50 minutes, and then 14 parts of diaminodiphenylmethane DDM were added and stirred at 60°C for 20-30 minutes. 8 parts of MWCNTs-SiO2 / CeO2 were added and stirred at high speed for 30 minutes. After mixing evenly, they were evenly sprayed on the outer surface of the composite inner layer pipe to form an outer protective layer. The mixture was cured at 100°C for 4 hours to finally obtain a double-layer pressure-bearing pipe.
[0048] Example 5 100 parts of continuous glass fiber bundles (Shandong Fiberglass Group Co., Ltd., 2400TEX, diameter 17 μm) and 50 parts of pretreated basalt fibers were soaked in 150 parts of composite coupling agent ethanol solution for surface treatment, dried in a vacuum oven at 80°C for 12 h, and excess moisture was removed. The mixture was poured into a composite mold and mixed evenly with 110 parts of molten high-density polyethylene (HDPE), and pressed into a strip by a roller to obtain a glass fiber / basalt fiber composite strip.
[0049] 65 parts of the composite coupling agent ethanol solution were added to 50 parts of the hollow glass microsphere suspension, and after magnetic stirring at 60°C for 4 hours, the mixture was separated by vacuum filtration, washed with ethanol solution for 3 times, and dried in a vacuum oven at 80°C for 12 hours to obtain the modified hollow glass microsphere (HGM). 110 parts of molten high-density polyethylene (HDPE) and 8 parts of modified hollow glass microspheres were mixed and stirred at high speed for 30 minutes to obtain the HGM / HDPE composite material. 100 parts of the molten HGM / HDPE composite material were extruded through an extruder to obtain the inner layer tube embryo, 60 parts of the glass fiber / basalt fiber composite tape were wound on the inner layer tube embryo in a winding manner of cross winding from both ends, and the wound tube obtained after winding was compounded at 400°C to obtain the composite inner layer tube.
[0050] 2.6 parts of 3-aminopropyltriethoxysilane (model: KH-550) were added to 100 parts of 90% ethanol solution and mixed evenly, then 2 parts of SiO2 and 2 parts of CeO2 were added and mixed evenly, stirred and reacted at 80°C for 6 hours, centrifuged for 5 minutes, the supernatant was discarded and the precipitate was dried at 80°C for 12 hours, and SiO2 / CeO2-NH2 was obtained after grinding; 1.5 parts of SiO2 / CeO2-NH2 were dispersed in 10 parts of water, 10 parts of pretreated MWCNTs-COOH were added and mixed, ultrasonically treated for 10 minutes, reacted at 80°C for 6 hours, washed, centrifuged, and dried at 80°C for 24 hours to obtain an aminated SiO2 / CeO2 composite filler.
[0051] 55 parts of preheated epoxy resin (model: E51) and 50 parts of butyl glycidyl ether were mixed at low speed for 40 minutes, and then 15 parts of diaminodiphenylmethane DDM were added and stirred at 60°C for 30 minutes. 5 parts of MWCNTs-SiO2 / CeO2 were added and stirred at high speed for 30 minutes. After mixing evenly, they were evenly sprayed on the outer surface of the composite inner layer pipe to form an outer protective layer. The mixture was cured at 100°C for 2 hours to finally obtain a double-layer pressure-bearing pipe.
[0052] Example 6 100 parts of continuous glass fiber bundles (Shandong Fiberglass Group Co., Ltd., 2400TEX, diameter 17μm) and 50 parts of pretreated basalt fibers were soaked in 150 parts of composite coupling agent ethanol solution for surface treatment, dried in a vacuum oven at 80°C for 12 hours, and excess moisture was removed. The mixture was poured into a composite mold and mixed evenly with 120 parts of molten high-density polyethylene (HDPE), and pressed into a strip by a roller to obtain a glass fiber / basalt fiber composite strip.
[0053] 65 parts of the composite coupling agent ethanol solution were added to 50 parts of the hollow glass microsphere suspension, and after magnetic stirring at 60°C for 4 hours, the mixture was separated by vacuum filtration, washed with ethanol solution for 4 times, and dried in a vacuum oven at 80°C for 12 hours to obtain the modified hollow glass microsphere (HGM). 100 parts of molten high-density polyethylene (HDPE) and 8 parts of the modified hollow glass microsphere were mixed and stirred at high speed for 20 minutes to obtain the HGM / HDPE composite material. 80 parts of the molten HGM / HDPE composite material were extruded by an extruder to obtain the inner layer tube embryo, and 55 parts of the glass fiber / basalt fiber composite tape were wound on the inner layer tube embryo in a winding manner of cross winding from both ends, and the wound tube obtained after winding was compounded at 400°C to obtain the composite inner layer tube.
[0054] 3.5 parts of 3-aminopropyltriethoxysilane (model: KH-550) were added to 100 parts of 90% ethanol solution and mixed evenly, then 2 parts of SiO2 and 2.5 parts of CeO2 were added and mixed evenly, stirred and reacted at 80°C for 5 hours, centrifuged for 5 minutes, the supernatant was discarded and the precipitate was dried at 80°C for 15 hours, and SiO2 / CeO2-NH2 was obtained after grinding; 1.5 parts of SiO2 / CeO2-NH2 were dispersed in 10 parts of water, 10 parts of pretreated MWCNTs-COOH were added and mixed, ultrasonically treated for 10 minutes, reacted at 80°C for 6 hours, washed, centrifuged, and dried at 80°C for 24 hours to obtain an aminated SiO2 / CeO2 composite filler.
[0055] 60 parts of preheated epoxy resin (model: E51) and 50 parts of butyl glycidyl ether were mixed at low speed for 30 minutes, and then 15 parts of diaminodiphenylmethane DDM were added and stirred at 60°C for 30 minutes. 10 parts of MWCNTs-SiO2 / CeO2 were added and stirred at high speed for 20 minutes. After mixing evenly, they were evenly sprayed on the outer surface of the composite inner layer pipe to form an outer protective layer. The mixture was cured at 100°C for 3 hours to finally obtain a double-layer pressure-bearing pipe.
[0056] The present invention also carries out comparative examples and related tests.
[0057] Comparative Example 1 The only difference compared with Example 1 is that no HGM / HDPE composite material is prepared, and the inner layer embryo is directly prepared using high-density polyethylene. The other components and preparation steps are completely the same, and a double-layer pressure-bearing pipe is obtained.
[0058] Comparative Example 2 The only difference compared with Example 1 is that the aminated modified SiO2 / CeO2 composite filler is not prepared as the outer protective layer filler, and SiO2 and CeO2 are directly added when preparing the outer protective layer filler, that is, 50 parts of preheated epoxy resin (model: E51) and 40 parts of butyl glycidyl ether are mixed at low speed for 30 minutes, and then 12 parts of diaminodiphenylmethane DDM are added and stirred at 60°C for 20 minutes, and 2.5 parts of SiO2 and 2.5 parts of CeO2 are added and stirred at high speed for 20 minutes to mix evenly, and then evenly sprayed on the outer surface of the composite inner layer pipe to form an outer protective layer. The other components and preparation steps are exactly the same, and finally a double-layer pressure-bearing pipe is obtained.
[0059] Comparative Example 3 The only difference compared with Example 1 is that the aminated modified SiO2 / CeO2 composite filler is not prepared as the outer protective layer filler, but the aminated modified SiO2 is prepared as the outer protective layer filler, and the other components and preparation steps are exactly the same to obtain a double-layer pressure-bearing pipe.
[0060] Comparative Example 4 The only difference compared with Example 1 is that the glass fiber / basalt fiber composite tape is not prepared, and the glass fiber tape is directly prepared. The other components and preparation steps are completely the same to prepare a double-layer pressure-bearing pipe.
[0061] Performance testing The double-layer pressure-bearing pipes prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to basic performance tests, and relevant tests were performed according to the standard CJ / T250-2018 for high-density polyethylene (HDPE) pipes and fittings for building drainage. The basic performance test results are shown in Table 1.
[0062] Table 1
[0063] It can be seen from Table 1 that the longitudinal shrinkage rate (110°C) of the pipes in Examples 1 to 6 is ≤3%, the melt mass flow rate is 0.2g / 10min≤≤1.1g / 10min, and the pipes are not broken in the impact strength test, which all meet the national standard CJ / T 250-2018.
[0064] Combined with the data analysis in Table 1, it can be seen that compared with Comparative Example 1, Example 1 has significantly improved bending strength and impact strength due to the addition of modified hollow glass microspheres. Comparative Example 2 has decreased impact strength and bending strength due to the lack of amination modification of SiO2 and CeO2. Comparative Example 3 shows that the amination modification of SiO2 improves its impact strength and bending strength compared with Comparative Example 2.
[0065] The double-layer pressure-bearing pipes prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to a heating test, a hydrostatic strength test, and a pipe ring stiffness test according to the standard CJ / T 250-2018 High-density polyethylene (HDPE) pipes and fittings for building drainage. The heating test was maintained at 110°C ± 2°C for 1 hour to observe changes in the pipe, and the hydrostatic strength test was maintained at 80°C and 4.6 MPa for 165 hours to observe changes in the pipe.
[0066] Table 2
[0067] As can be seen from Table 2, through the heating test, it can be concluded that in Comparative Example 2, since SiO2 and CeO2 were not aminated and modified, stratification and blistering occurred when SiO2 and CeO2 were directly used as outer protective layer fillers, and the ring stiffness and bursting pressure were also significantly reduced. In Comparative Example 3, the aminated SiO2 was added to improve the ring stiffness, bursting pressure and hydrostatic strength of the outer protective layer. The addition of modified hollow glass microspheres and glass fiber / basalt fiber composite tapes in Example 1 made it significantly better than Comparative Example 1 and Comparative Example 4 in the pipe ring stiffness, bursting pressure and hydrostatic strength tests.
[0068] The outer protective layers prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to relevant tests with reference to GB / T 34202-2017, wherein the chemical corrosion resistance was the test result of exposure to an acid solution and an alkaline solution for 6 days each, the wear resistance was the wear thickness after 500 cycles, and the heat aging resistance test in water was the adhesion of the coating after the test. The test results are shown in Table 3.
[0069] Table 3
[0070] It can be seen from Table 3 that the adhesion, heat aging resistance, chemical corrosion resistance and wear resistance of the outer protective layers prepared in Examples 1 to 6 are significantly improved; in Comparative Example 2, since the aminated SiO2 / CeO2 composite filler was not prepared, SiO2 and CeO2 were directly added as fillers for the outer protective layer, which significantly reduced the adhesion and wear resistance of the prepared outer protective layer; in Comparative Example 3, since CeO2 was not added to prepare the aminated SiO2 / CeO2 composite filler, the lack of CeO2 significantly reduced the heat aging resistance and chemical corrosion resistance of the outer protective layer in water.
[0071] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a double-layer pressure-bearing pipe, characterized in that: The following steps are involved: S1, soaking the continuous glass fiber bundle and the pretreated basalt fiber in a composite coupling agent ethanol solution for surface treatment, vacuum drying, pouring into a composite mold and mixing with molten high-density polyethylene, and pressing into a strip by a roller to obtain a glass fiber / basalt fiber composite strip; S2, mixing molten high-density polyethylene and modified hollow glass microspheres at high speed to obtain HGM / HDPE composite material, extruding the molten HGM / HDPE composite material through an extruder to obtain an inner layer pipe embryo, winding a glass fiber / basalt fiber composite tape on the inner layer pipe embryo, and compounding at 380-400° C. to obtain a composite inner layer pipe; S3. Mix the preheated epoxy resin and butyl glycidyl ether at a low speed, add diaminodiphenylmethane and stir at a high temperature, add the aminated modified SiO2 / CeO2 composite filler and stir at a high speed to mix evenly, spray it on the outer surface of the composite inner layer pipe to form an outer protective layer, cure it at a high temperature, and finally obtain a double-layer pressure-bearing pipe.
2. The method for preparing a double-layer pressure-bearing pipe according to claim 1, characterized in that: The pretreated basalt fiber in step S1 is prepared by adding chopped basalt fiber material into a sulfuric acid solution with a mass concentration of 3%, stirring and reacting at 80° C. for 30 minutes, taking out, filtering and drying.
3. The method for preparing a double-layer pressure-bearing pipe according to claim 1, characterized in that: The vacuum drying time in step S1 is 12 hours and the temperature is 80°C; the composite coupling agent ethanol solution is prepared by mixing a titanate coupling agent and a silane coupling agent in a volume ratio of 1:1 to prepare a composite coupling agent, adding the composite coupling agent to an ethanol solution with a volume concentration of 90%, mixing evenly, and adjusting the pH value to 5.0 with glacial acetic acid; wherein the model of the titanate coupling agent is CS201, and the model of the silane coupling agent is KH540.
4. The method for preparing a double-layer pressure-bearing pipe according to claim 1, characterized in that: The modified hollow glass microspheres in step S2 are prepared by mixing a composite coupling agent ethanol solution and a hollow glass microsphere suspension, stirring the mixture by magnetic force, separating the mixture by vacuum filtration, washing the mixture with an ethanol solution for 3 to 5 times, and vacuum drying the mixture.
5. The method for preparing a double-layer pressure-bearing pipe according to claim 4, characterized in that: The magnetic stirring temperature is 60° C. and the time is 4 hours, and the vacuum drying temperature is 80° C. and the time is 12 hours; the hollow glass microsphere suspension is prepared by mixing an ethanol solution with a volume concentration of 90% and hollow glass microspheres, and then subjecting the mixture to ultrasonic treatment for 45 minutes.
6. The method for preparing a double-layer pressure-bearing pipe according to claim 1, characterized in that: In the step S2, the glass fiber / basalt fiber composite tape is wound on the inner layer tube blank in a winding manner of cross winding from both ends, and the wound tube obtained after winding is compounded at 380-400° C. to obtain a composite inner layer tube.
7. The method for preparing a double-layer pressure-bearing pipe according to claim 1, characterized in that: The aminated SiO2 / CeO2 composite filler in the step S3 is prepared by mixing a 90% volume concentration ethanol solution and 3-aminopropyltriethoxysilane, adding SiO2 and CeO2 and mixing evenly, stirring and reacting at 80°C for 4-6 hours, centrifuging for 5 minutes, discarding the supernatant and taking the precipitate, drying at 80°C for 12-16 hours, grinding to obtain SiO2 / CeO2-NH2, and dispersing SiO2 / CeO2-NH2 in water.
8. The method for preparing a double-layer pressure-bearing pipe according to claim 7, characterized in that: After dispersing SiO2 / CeO2-NH2 in water, pretreated MWCNTs-COOH is added and mixed, and then ultrasonic treatment is performed for 10-20 minutes. After reacting at 80°C for 6-10 hours, the mixture is washed, centrifuged, and dried at 80°C for 24-48 hours to finally obtain an aminated SiO2 / CeO2 composite filler; wherein the pretreated MWCNTs-COOH is obtained by mixing and stirring a MWCNTs-COOH aqueous dispersion, a 10% mass concentration of 1-ethyl-(3-dimethylaminopropyl)carbodiimide aqueous solution, and a 10% mass concentration of 0.1 parts of N-hydroxysuccinimide aqueous solution for 10 minutes; and the MWCNTs-COOH aqueous dispersion is obtained by adding MWCNTs-COOH into water and ultrasonicating for 1 hour.
9. The method for preparing a double-layer pressure-bearing pipe according to claim 1, characterized in that: The low-speed mixing time in step S3 is 30-60 minutes, the high-temperature stirring temperature is 60° C. and the time is 20-30 minutes, the high-speed stirring time is 20-30 minutes, and the high-temperature curing temperature is 80-100° C. and the time is 2-5 hours.
10. Double-layer pressure-bearing pipe, characterized in that: The double-layer pressure-bearing pipe is prepared by the preparation method of any one of claims 1 to 9, comprising the following raw materials in parts by weight: 50 to 60 parts of preheated epoxy resin, 40 to 50 parts of butyl glycidyl ether, 12 to 15 parts of diaminodiphenylmethane, 5 to 10 parts of MWCNTs-SiO2 / CeO2, and 100 to 120 parts of a composite inner layer pipe; wherein the composite inner layer pipe comprises the following raw materials in parts by weight: 80 to 100 parts of HGM / HDPE composite material and 50 to 60 parts of glass fiber / basalt fiber composite tape.